INCREASED MIDDLE CEREBRAL ARTERY PULSATILITY IN PATIENTS WITH LEUKOARAIOSIS: ENHANCED TRANSMISSION OF AORTIC PULSE WAVES DUE TO INCREASED ARTERIAL STIFFNESS. (29th November 2012) - Webb, A; Simoni, M; Rothwell, PM
Abstract : Background: Arterial stiffening results in reduced damping of the pulse and increased cerebral arterial pulsatility, which may damage small vessels. We determined the association between leukoaraiosis and aortic and middle cerebral artery stiffness and pulsatility. Methods: Patients were recruited from the Oxford Vascular Study within 6 weeks of a TIA or minor stroke. Leukoaraiosis was assessed on MRI by the Fazekas and ARWMC scales. MCA transit time (MCA-TT) and pulsatility (MCA-PI) were measured with TCD, whilst aortic pulse wave velocity (ao-PWV) and aortic systolic, diastolic and pulse pressure (SBP, DBP, PP) were measured by applanation tonometry. Results: In 100 patients, MCA-PI was greater in patients with leukoaraiosis (0.91 vs 0.73, p<0.001). Severity of leukoaraiosis correlated with MCA-PI and ao-PWV (Fazekas: r 2 =0.340, MCA-PI p<0.001, ao-PWV p=0.038; ARWMC: r 2 =0.239, MCA-PI p<0.001) for periventricular and deep white matter lesions, independent of age, sex and other measurements. MCA-PI was independently associated with aortic DBP and PP, ao-PWV and MCA-TT (r 2 =0.654, ao-PP p<0.0001, ao-DBP p<0.0001, MCA-TT p=0.001, ao-PWV p=0.019). Conclusions: MCA pulsatility was the strongest correlate of leukoaraiosis, independent of age. It was dependent upon aortic DBP and PP and aortic and MCA stiffness, suggesting the hypothesis that aortic stiffening results in increased pulsatility and its transmission to the cerebral vessels, causing leukoaraiosis.